System for Development of "Foreign Language for Specific Purposes" at Polytechnic University (German Language Case) - Zabrodina I. K. Irina Konstantinovna; Bychkov P. N. Petr Nikolaevich; Perminova M. V. Mariya Viktorovna; Karmanova Yu. A. Yuliya Alexandrovna (2016, 2016)
Title screen